Hubungan Spiritual Well-Being dengan Burnout Pada Perawat - Alifiya, Innazza Nur; Susanti, Indri Heri; Murniati, Murniati (JURNAL KEPERAWATAN RAFLESIA, 2023)
Nursing is a profession that is prone to burnout. One that influences burnout is spiritual. Spiritual emptiness will cause individuals to feel various negative emotions, such as emptiness in life, easy to give up and complain when experiencing problems. The study aims to determine the relationship between spiritual well-being and burnout among nurses at RSUD Dr. R. Goeteng Taroenadibrata Purbalingga. This research method is correlated with cross-sectional approach. Respondents in the study were 119 inpatient nurses who were taken by total sampling technique. Data were collected using the Spirituality Well-Being Scale (SWBS) questionnaire and The Maslach Burnout Inventory-Human Service Survey (MBI-HSS) questionnaire. Data analysis showed that the spiritual well-being level of nurses was dominated by the high category of 117 respondents (98.3%). The majority of nurses experienced low level of burnout (95%). The results of the study showed that there was a moderate relationship between spiritual well-being and burnout among nurses at RSUD Dr. R. Goeteng Taroenadibrata Purbalingga. Correlation test results obtained a p-value of 0.000 and a Rho value of -0.567, then the higher the spiritual level of well-being, the lower the level of burnout. Therefore, high spiritual well-being can prevent burnout in nurses.